(3GdQSGdI GdLGeYI PGJ GdahGFO GdfGaYI JGL QSGFd GNhGf GdUaGs - (3eSdeI Hf CMeO Hf bGSe Hf YHO Gddg GdeLQjWj, CHh GdbGSe,J (B398 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb aShi EYde CjgG GdCN GdHGQ EfG bO bOefG Edjc ef CfhGQ GdMce hdWGja GdfYe s
(3BNQgG (B:s
(3hGYde Cf djS ddEfSGf EdG eG SYi aEf SYjg Sha jfgi Ke fLRGg GdLRGA GdChai hEf Edi QHc GdefJgi fLRJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B234s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B902s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs